Performance comparison between different channel models with channel estimation and adaptive equalization using Rayleigh fading channel - zabin, Broty; Imon, Imtiaz Ahmed (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2008.